Understanding Volume Kinetics: The Role of Pharmacokinetic Modeling and Analysis in Fluid Therapy - Yiew, Xiu Ting; Bateman, Shane W.; Hahn, Robert G.; Bersenas, Alexa M. E.; Muir, William W. (Frontiers in Veterinary Science, 2020)
Fluid therapy is a rapidly evolving yet imprecise clinical practice based upon broad assumptions, species-to-species extrapolations, obsolete experimental evidence, and individual preferences. Although widely recognized as a mainstay therapy in human and veterinary medicine, fluid therapy is not always benign and can cause significant harm through fluid overload, which increases patient morbidity and mortality. As with other pharmaceutical substances, fluids exert physiological effects when introduced into the body and therefore should be considered as “drugs”. In human medicine, an innovative adaptation of pharmacokinetic analysis for intravenous fluids known as volume kinetics using serial hemoglobin dilution and urine output has been developed, refined, and investigated extensively for over two decades. Intravenous fluids can now be studied like pharmaceutical drugs, leading to improved understanding of their distribution, elimination, volume effect, efficacy, and half-life (duration of effect) under various physiologic conditions, making evidence-based approaches to fluid therapy possible. This review article introduces the basic concepts of volume kinetics, its current use in human and animal research, as well as its potential and limitations as a research tool for fluid therapy research in veterinary medicine. With limited evidence to support our current fluid administration practices in veterinary medicine, a greater understanding of volume kinetics and body water physiology in veterinary species would ideally provide some evidence-based support for safer and more effective intravenous fluid prescriptions in veterinary patients.